(3EOGQI efGaP GdJhRjY(B((3eONd hUaj JMdjdj(B)s - (3LeGd GdOjf eMeO(B, (3GdeQSjs; (3KGHJ(B, (3YHO GdQMef EOQjSs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2007)
(3WHjYI GdJShjb,GdJShjb cYedjI JHGOd,efTBJ JLGQI GdLedI,efTBI JLGQI GdJLRFI(B((3GdhXGFa hGdJbSjeGJ GdefGaSI,efTBJ GdJLRFI(B((3GdJNWjW GdGSJQGJjLj(B)(3,GdGWGQ GdYGe dfTWI efTBJ GdJhRjY GdeGOj,efTBJ GdJhRjY GdeGOj(B((3eDSSGJ Gdfbd(B)(3,efTBJ GdJhRjY GdeGOj(B((3GdeNGRf hGOGQI GdeNRhf(B)(3,GdGfTWI GdGNQi defTBJ GdJhRjY GdeGOj,hcGdGJ GdGYdGf,af GdHjY aj efTBJ GdJLRFI,egGQGJ GdJaGhV ddYGedjf aj GdefTBJ GdJShjbjIs
(3HHdjhZQGajG(B:(3U(B.545-549s
Keywords: (3GdJShjbs